GAMBARAN TUMPATAN AMALGAM DAN SEMEN IONOMER KACA PADA MASYARAKAT KELURAHAN KALUMPANG KECAMATAN TERNATE TENGAH - Marhaban, Andi I. A.; Mintjelungan, Christy; Supit, Aurelia (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Until now, dental caries is a major issue in dental health problems. Dental restoration is a conservative effort to reduce caries index. Dental restoration is done by putting the restorative material into cavities that have been cleaned and prepared. Restorative materials vary depending on the location and function of the tooth. Restorative materials that are commonly used in community health centers are amalgam and glass ionomer cement (GIC). This study aimed to determine the description of amalgam and GIC restoration and the reason for using it, as well as evaluating the patients’satisfaction concerning the result of dental restoration at Kalumpang, Central Ternate District. This was a descriptive study with a cross-sectional design. Total samples were 100 individuals who were selected by using a purposive sampling method. Data retrieval was done by physical examination and questionnaires. The results showed that from the 100 samples, there were 65% who had amalgam restoration and 35% with GIC restoration. It was found that 92.31% of the respondents were satisfied with the result of the amalgam restoration, and 82.86% of the respondents were satisfied with the result of the GIC restoration. Conclusion: The majority of the respondents at Kalumpang, Central Ternate District, were satisfied with the aesthetics, function, strength, and durability of both the amalgam and GIC restoration results. Of those included in the study, only a small percentage of the respondents had their amalgam or GIC restorations at the local community health center at Kalumpang. Keywords: amalgam restoration, glass ionomer cement (GIC) restoration Abstrak: Sampai saat ini masalah kesehatan gigi yang banyak ditemukan yaitu kasus karies gigi dengan prevalensi yang cukup tinggi di berbagai daerah. Penumpatan gigi merupakan salah satu upaya konservatif untuk menurunkan indeks karies. Penumpatan gigi ialah suatu tindakan perawatan dengan cara meletakkan bahan tumpat pada gigi berlubang yang sudah dibersihkan. Bahan tumpat bervariasi tergantung letak dan fungsi gigi tersebut.Tumpatan yang umum digunakan di puskesmas yaitu tumpatan amalgam dan semen ionomer kaca (SIK). Penelitian ini bertujuan untuk mengetahui gambaran tumpatan amalgam dan SIK, alasan penggunaan tumpatan, dan kepuasan terhadap tumpatan yang digunakan pada masyarakat Kelurahan Kalumpang Kecamatan Ternate Tengah. Penelitian ini bersifat deskriptif dengan menggunakan cross-sectional design. Jumlah sampel sebanyak 100 orang yang diambil secara purposive sampling. Pengambilan data dilakukan dengan pemeriksaan langsung dan pengisian kuisioner. Hasil penelitian memperlihatkan bahwa dari 100 sampel, terdapat 65% yang menggunakan tumpatan amalgam dan 35% tumpatan SIK. Sejumlah 92,31% responden puas dengan hasil tumpatan amalgam dan 82,86% yang puas dengan hasil tumpatan SIK. Simpulan: Sebagian besar responden di Kelurahan Kalumpang Kecamatan Ternate Tengah baik yang menggunakan amalgam maupun SIK menyukai estetik, fungsi, kekuatan, dan keawetan bahan tumpatan tersebut dan puas dengan hasil tumpatan. Sebagian kecil dari responden ditumpat baik dengan amalgam maupun SIK di Puskesmas Kalumpang. Kata kunci: tumpatan amalgam, tumpatan SIK